2018
DOI: 10.17482/uumfd.373302
|View full text |Cite
|
Sign up to set email alerts
|

Sizinti Suyu Aritiminda Strüvi̇t Çöktürme Opti̇mi̇zasyonu

Abstract: Sanitary landfill is the most preferred municipal solid waste disposal method. The production of highly polluted leachate is a major disadvantage of sanitary landfills. In this study, optimization of struvite precipitation to remove ammonium from landfill leachate was conducted by using Response Surface Methodology and central composite design. Optimum struvite precipitation conditions were determined based upon 11 runs performed in central composite design. A second-order polynomial functional model was fitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Several studies confirmed that the most widely applied physicochemical processes were coagulation/flocculation, [ 18,19 ] chemical precipitation, [ 19 ] reverse osmosis, [ 20 ] and photocatalysis. [ 21 ] These methods were found to be suitable for the degradation of refractory compounds from mature LFL.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies confirmed that the most widely applied physicochemical processes were coagulation/flocculation, [ 18,19 ] chemical precipitation, [ 19 ] reverse osmosis, [ 20 ] and photocatalysis. [ 21 ] These methods were found to be suitable for the degradation of refractory compounds from mature LFL.…”
Section: Introductionmentioning
confidence: 99%